2020 K-State Industrial Hemp CBD Variety Trial - Jason Griffin; Clint Wilson; Tami Myers (Kansas Agricultural Experiment Station Research Reports, 2021)
Hemp is a broad term used to describe the many varieties ofCannabis sativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently was allowed to be grown once again in the United States. Varieties have been selected and are currently grown with a wide cannabinoid profile. Cannabinoids are of high interest for their putative medical and therapeutic role in humans and companion pets. Cannabidiol (CBD) and THC are the two cannabinoids of primary interest. THC is of interest because it determines whether the final product is considered hemp (0.3% THC). CBD is of interest because of its potential therapeutic properties and its legal status across many states. Currently, there is no information available regarding adaptability or cannabinoid production of these varieties in Kansas. In 2020, Kansans were allowed to apply for research licenses to grow industrial hemp for the second year. There are wild remnant populations ofC. sativaflourishing at numerous locations across the state, so it was no surprise that hemp grew successfully in 2019. Controlled variety trials are necessary to determine which varieties are best adapted to Kansas and which methods produce the greatest yield. Currently, growers must rely on only one growing season’s data in Kansas or information generated from other states with vastly different growing conditions. Variety selection is vital in CBD hemp production, considering that environmental conditions strongly influence cannabinoid ratios and ultimately, total cannabinoid content. The objective of this study was to evaluate the date of potting of three commercially available varieties of CBD hemp in south-central KS grown in containers inside a high tunnel. Flowering of hemp is light sensitive. Therefore, regardless of when plants are propagated and potted, if exposed to natural photoperiod they should mature and flower at the same time. Potting plants earlier in the season should yield larger plants. However, larger plants are not always ideal given cultural requirements to support large plants and potential extended exposure to pests and diseases.
Keywords: Cannabis; cannabidiol; high tunnel; planting date